The role of electrocochleography and the caloric test in predicting short-term recurrence of benign paroxysmal positional vertigo - Zhang, Yanmei; Wang, Yueqi; Zhen, Zhen; Zhang, Junbo; Zeng, Zhengang; Zhong, Zhen; Wang, Quangui (Frontiers in Neurology, 2023)
Objective The study aimed to assess the value of physiological tests for evaluating inner ear function in predicting the short-term recurrence of benign paroxysmal positional vertigo (BPPV). Materials and methods The clinical information of all idiopathic BPPV patients who were treated in our clinic between February 2021 and December 2022 were reviewed. All patients included in the study had completed audiology examinations including pure tone audiometry, electrocochleography (EcochG), auditory brainstem response, and vestibular function examination such as the vestibular caloric test. The relationships between the results of the above tests and short-term recurrent BPPV were analyzed. Results A total of 96 patients with unilateral idiopathic BPPV were included for analysis. The numbers of non-recurrent patients and recurrent patients were 57 (59.4%) and 39 (40.6%), respectively. Only the results of EcochG and the caloric test showed significant differences between non-recurrent and recurrent patients (both P < 0.05). The results of these two tests were also found to be independently predictive of short-term recurrence (both P < 0.05). The non-recurrence rate for patients with normal results in both tests reached up to 78.3%, which was significantly higher than that for patients with abnormal results in both tests, 28.6% (P < 0.05). Conclusion Endolymphatic hydrops and canal paresis were independent risk factors for short-term recurrent BPPV. Additional treatments should be considered to reduce the recurrence rate, including dehydration treatment and vestibular rehabilitation.